Induction of uterine hyperplasia after cafeteria diet exposure - Gastiazoro, Maria Paula (2018)
Our aim was to evaluate whether chronic administration of CAF affects the uterus and induces the morphological and molecular changes associated with endometrial hyperplasia. Female Wistar rats exposed to CAF from weaning for 20 weeks displayed increased energy intake, body weight and fat depots, but did not develop metabolic syndrome. The adult uteri showed an increase in glandular volume fraction and stromal area. The epithelial proliferation rate and protein expression of oestrogen receptor alpha (ERα) were also increased. The CAF diet enhanced leptin serum levels and the long form of leptin receptor (Ob-Rb) mRNA expression in the uterus. No changes were detected in either insulin serum levels or those of insulin growth factor I (IGF-I) mRNA expression. However the levels of IGF-I receptor (IGF-IR) mRNA were lower in CAF-fed animals. Overall, the results indicate that our rat model of the CAF diet produces morphological and molecular changes associated with uterine hyperplasia and could predispose to endometrial carcinogenesis.